Condições do trabalho docente na perspectiva de professores do Município de São Paulo - Peruchi, Viviani Souza (2017)
Introduction: being a teacher is working at risk for the presence of the voice disorder. Biological factors, related to those present in the environment and in the organization of work deserve attention in the prevention and treatment of vocal problems. The City Hall of São Paulo, in partnership with the Voice Laboratory of the Pontifical Catholic University of São Paulo, has offered a distance learning course (EAD) to sensitize teachers about these issues. Objective: to analyze the conditions of teaching work from the perspective of teachers in the city of São Paulo. Method: 300 teachers participated in the fourth group of the EAD course entitled "Promoting Vocal Well-being of the Teacher" occurred in the second half of 2015. After considering the inclusion criteria (being a teacher in a teaching activity), 142 teachers were part of the sample. The course, lasting 40 hours, was composed of eight modules, eight forums and eight evaluations (inserted in the Moodle Platform), as well as three face-to-face meetings. In module 3 the teachers were invited to elaborate a material in which they spontaneously described the main aspects concerning the situation regarding their current context of work. This material was registered on the São Paulo City Hall platform and, after careful reading, categorized according to the factors of the environment and work organization mentioned. These were associated with age, time of experience, level of performance, bond (teacher) and hourly load (Chi-square p = 5%). Results: The sample had 96.5% of female participants. The mean age was 39.8 years (SD = 8.1), median of 39.1, ranging from 28.6 to 62.7 years. The most important factors related to the environment were noise, dust and temperature, as well as the organization of work, lack of commitment, inadequate teaching materials and stress. Conclusion: For the group of teachers analyzed, the environmental factors that interfere with their work are presence of noise (for those with more than 10 years of experience), inadequate temperature (for those who work less than 10 years and those who teach for The level of fundamental II) and inadequate cleaning (for the elderly and for the substitutes). Concerning the factors related to work organization, the lack of time to develop the activities (for the elderly and those who teach in the fundamental II), lack of commitment (by those who work less than 20 hours a week) and violence Who has been working for over 10 years)